Will the rise of Sci-Hub pave the road for the subscription-based access to publishing databases?. (November 2017) - Strielkowski, Wadim
Sci-hub has become the new phenomenon on the academic publishing market. While its popularity is growing worldwide, large academic publishers are losing millions of dollars on paid article downloads. Perhaps the time has come to re-think the rules of the game of the publishing market and to look for novel solutions for monetizing scientific output. Subscription-based access to publishing databases, similar to the model used in online music streaming, might be one of these solutions that could secure the status quo and stabilize the market.